Ответы и объяснения

Лучший Ответ!
2013-02-13T14:19:14+04:00

Домножим на сопряженные множители:

 

 

\frac{1}{\sqrt{2}+1}+\frac{1}{\sqrt{3}+\sqrt{2}}+...+\frac{1} {\sqrt{100}+\sqrt{99}}=\frac{1(\sqrt{2}-1)}{(\sqrt{2}+1)(\sqrt{2}-1)}+\frac{1(\sqrt{3}-\sqrt{2})} {(\sqrt{3}+\sqrt{2})(\sqrt{3}-\sqrt{2})}+...\frac{1(\sqrt{100}-\sqrt{99})}{(\sqrt{100}+\sqrt{99}) (\sqrt{100}-\sqrt{99})}=\frac{\sqrt{2}-1}{1}+\frac{\sqrt{3}-\sqrt{2}}{1}+...+\frac{\sqrt{100}- \sqrt{99}}{1}=\frac{\sqrt{2}-1+\sqrt{3}-\sqrt{2}+..+\sqrt{100}-\sqrt{99}}{1}=\sqrt{100}-1=10-1=9

 

 

Равенство верно.